Reflection in a high-performance sport coach education program: A Foucauldian analysis of coach developers - Downham, L.; Cushion, C. (International Sport Coaching Journal, 2020)
Reflection is a contested but taken for granted concept, whose meaning shifts to accommodate the interpretation and interests of those using the term. Subsequently, there is limited understanding of the concept. The purpose of this article was to consider critically the discursive complexities of reflection and their articulation through coach developers` practice. Data were collected from a National High-Performance coach education program. Coach developers responsible for one-to-one support (n=8) and on-program support (n=3) participated in the research. Semistructured interviews were conducted with coach developers, and participant observations were undertaken of a coach developer forum and program workshops (n=9). Foucault`s concepts: power, discourse, and discipline were used to examine data with critical depth. Analysis explored "Discourse of Reflection," "Discipline, Power, and Reflection," and "Coach Developers: Confession, `Empowerment,` and Reflection." Humanistic ideas constructed a discourse of reflection that was mobilized through coach confession. Coach developer efforts to be "critical" and "learner centered" were embroiled with intrinsic and subtle relations of power as "empowering" intent exacerbated rather than ameliorated its exercise. This article makes visible a different destabilized and problematized version of reflection, thus introducing an awkwardness into the fabric of our experiences of reflection.